'Mad', Mad studies and advancing inclusive resistance. Issue 8 (13th September 2020) - Beresford, Peter
Abstract: 'Mad' is a contentious term with which many service users/survivors feel uncomfortable. Yet it is the framework for a major new user-led challenge to bio-medical thinking about distress – Mad Studies – which is coming in for criticism for this and other identified shortcomings. Why has it adopted this controversial, conflict-ridden title? This article will explore current criticisms and raise the question of what Mad Studies' strategy should be to address them for the future?